Comparative Efficacy of Pedagogical Approaches in Fostering Sustainable Entrepreneurship Among Youth Learners in Botswana - Sangodoyin, Oluranti Olukemi; Sibanda, Khulekani; Masoabi, Palesa (International Journal of Business, Management and Economics, 2026)
Research Aims: This study aimed to identify effective pedagogical strategies to foster sustainable entrepreneurship among secondary school students in Botswana, thereby addressing high youth unemployment and environmental crises. Design/methodology/approach: A 12-week quasi-experimental mixed-methods study was conducted with 180 students from six secondary schools. Students were divided into three groups: experiential learning, problem-based learning (PBL), and traditional lecture-based teaching. Quantitative data was collected using pre- and post-intervention questionnaires to measure entrepreneurial intention, sustainability literacy, and innovation orientation. Qualitative data was gathered through classroom observations and focus groups to understand student perceptions. Research Findings: The findings revealed that both PBL and experiential learning significantly outperformed the lecture-based method (p<0.001). Experiential learning showed the most substantial gains across all measured competencies. Qualitative results supported this, as students in the active learning groups valued the real-world relevance and collaborative activities, while the lecture group felt the material was disconnected from practice. The study also found that female and urban learners responded more positively to active learning strategies. Theoretical Contribution/Originality: This study provides strong evidence for the effectiveness of PBL and experiential learning in promoting sustainable entrepreneurship in a secondary school context. It highlights the need for curricular reform in Botswana to incorporate these active learning strategies and to address challenges such as teacher training and rigid assessment methods